A DIFFERENTIATED ALGORITHM FOR SURGICAL METHOD SELECTION AND EARLY REFERRAL TO ASSISTED REPRODUCTION IN VARICOCELE-ASSOCIATED INFERTILITY (Global Conference on Multidisciplinary Research and Innovation, 2026)
The choice of surgical method for varicocele is often based on surgeon preference rather than on the hemodynamic source of reflux and the patient’s prognostic profile, while the limited availability and high cost of assisted reproductive technologies make the rational selection of candidates for surgery particularly important. An integrated algorithm linking method selection to reflux type and prognosis is therefore needed.